Managing Large Perforated Internal Root Resorption With Partial Pulpectomy: A Case Report - Saeed Asgary (Clinical Case Reports)
ABSTRACT Internal root resorption (IRR) is a complex and often asymptomatic dental condition that can severely compromise tooth vitality and function. This case report presents the successful management of a perforated large IRR lesion in a 49‐year‐old female using an ultraconservative approach involving partial pulpectomy (PP) using calcium‐enriched mixture (CEM) cement. The patient, initially presenting with an asymptomatic resorptive lesion in her left first premolar, underwent ultraconservative PP following diagnosis via conventional radiography and cone beam computed tomography. Despite encountering excessive bleeding during treatment, the tampon technique using CEM cement allowed reasonable hemostasis and effective sealing of the pulp stump, facilitating the preservation of tooth structure. Follow‐up at 2 weeks and 2 years showed positive outcomes, including cessation of the resorptive process and normal periodontal health. This case demonstrates the efficacy of vital pulp therapy, specifically partial pulpectomy, in managing advanced IRR and underscores the potential for tooth preservation and long‐term stability through an ultraconservative approach.